Evaluating Chlorophyll-a Changes During Algal Bloom in Three Gorges Reservoir Using an Extended WASP Model - Li, Jian (2016)
Algal bloom in Three Gorges Reservoir (TGR) and one of its tributaries, Xiangxi River (XR), have become major concerns and the dynamic changes of such events were investigated using the hydrodynamic model SELFE and the extended Water Quality Analysis Simulation Program (WASP) model to address nutrient and biomass dynamics. The model has taken into consideration the surface wind, heat fluxes, oxygen exchanges, solar radiations and boundary conditions from main river channel and tributaries. As an extension to our previous work, this study aimed to report in more detailed the result of chlorophyll-a simulations, where the field observed data of algal blooms in TGR in 2007 was used for calibration and the horizontal and vertical distributions of phytoplankton biomass (based on chlorophyll-a) were presented. It was found that the chlorophyll-a concentration characterized as algal biomass was influenced by many complex factors. Further study results are yet to be reported.